Comparative Study of Fast Focus Mode and Slow Focus Mode in Plasma Focus Devices - Damideh, Vahid (2016)
In this thesis comparison between Fast Focus Mode (FFM) and Slow Focus Mode (SFM) in plasma focus devices is studied. For INTI PF machine, results of numerical experiments based on Lee Model Code on Deuterium, Neon and Argon in the pressure range of 1Torr to 14 Torr D, 1 Torr to 5.5 Torr Ne and 0.2 Torr to 2.4 Torr Ar show that as a rule-of-thumb, diameter-optimized SFM is considered to occur when fast plasma stream speed generated by pinch column is equal to the peak axial phase speed. Results of speed factor, FIB energy, FPS energy, FIB damage factor, plasma footprint radius for FFM and SFM at different pressures of D, Ne and Ar are presented. These results may be used to predict different applications of both modes: especially in the fields of nuclear fusion reactor first wall materials and its related investigations by time-matched FFM; and thin film nano-material synthesis by diameter-optimized SFM. Design and construction of a PMT-Scintillator diagnostic system for D-D fusion Neutron time-of-flight measurements (TOF) in INTI PF machine are presented. In addition, a fast 50 Ω Faraday Cup was designed and fabricated to enable time-of-flight TOF measurements of pulsed ion beam of INTI PF. The shortest FWHM for ion pulse captured by Faraday Cup was 27 ns. In this research the correlation of the ion beam energy between TOF measurements and Lee Model Code with different kind of filling gases such as D, Ne, Ar, Kr and Xe is presented. The results show there is acceptable correlation between TOF measurements and Lee Model Code. The maximum most common energy for D, Ne, Ar, Kr and Xenon ions generated by pinch column, detected by Faraday Cup were 67 keV, 485 keV, 1.2 MeV, 3.9 MeV and 6 MeV consistent with the values predicted by Lee Model Code. In the cases of Ar, Kr and Xe, Radiative Collapse effect leads to very small pinch radius size which is calculated by Lee Model Code. In order to study the application of INTI plasma focus machine in the field of advanced material sciences, some experiments such as graphite deposition on silicon wafer, hardening by nitriding and also fusion first wall material research by using tungsten targets are presented. Conceptual design of 160 kJ DuPF as a biggest plasma focus facility in the world for material research, by using Lee Model code in both FFM and SFM at different pressures of different kind of filling gases such as D, Ne and Ar is presented. It seems that reliable SFM for all gases occur when the ratio of FPS speed to axial velocity is near to 1. Finally, industrial detail design of DuPF and its parts by using SolidWorks software is presented.